The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jocd.12528
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of skin anti‐aging clinical benefits of an association of ingredients from marine and maritime origins: Ex vivo evaluation using a label‐free quantitative proteomic and customized data processing approach

Abstract: These results suggest that the tested ingredients could help to preserve a healthy epidermis and dermis, and possibly to prevent the visible signs of skin aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…With this as motivation, we performed a time-course experiment to verify the effects QB on the epidermis in vitro 27 . We opted for the Reconstructed Human Epidermis (RHE) cell culture as this system mimics the in vivo 3D structure of epidermal tissue as well as the conditions and processes that occur in exposure to exogenous factors 23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this as motivation, we performed a time-course experiment to verify the effects QB on the epidermis in vitro 27 . We opted for the Reconstructed Human Epidermis (RHE) cell culture as this system mimics the in vivo 3D structure of epidermal tissue as well as the conditions and processes that occur in exposure to exogenous factors 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Proteomics has served at the forefront as a tool for the development and evaluation of innovative cosmetic products 23 , 24 . Here, we investigated the proteomic alterations in human epidermis tridimensional (3D) cell culture (RHE), co-cultivated with dermal fibroblasts, after 0 h, 3 h, 6 h, 12 h, 24 h, and 48 h of exposure to quinoa bioester (QB); comparisons were performed with unexposed counterparts at the same time points.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of mixtures of components has been described. Hameury et al [323] confirmed that an association of ingredients from marine origin revealed activity on the epidermis and the dermis, by regulation of proteins involved in gene expression, cell survival and metabolism, inflammatory processes, dermal extracellular matrix synthesis, melanogenesis and keratinocyte proliferation, migration, and differentiation, thus helping to prevent the visible signs of skin aging.…”
Section: Uv Protection Antioxidant and Antiagingmentioning
confidence: 96%
“…Due to its fast growth rate and high polysaccharide content, including mannitol and alginate, giant kelp is a great candidate as feedstocks for biofuels (Camus et al, 2016). Giant kelp can also be used as an animal feed supplement and has extractable bio-active compounds that can be used in a wide variety of applications, such as fertilizer supplement to cosmetics to antioxidant activity (Arioli et al, 2015;Makkar et al, 2016;Tanna and Mishra, 2018;Hameury et al, 2019). Seaweed domestication has been hampered by limited starting gene pools and clonal propagation techniques.…”
Section: Introductionmentioning
confidence: 99%